Application of biochar activated persulfate in the treatment of typical azo pigment wastewater. (15th December 2022) - An, Qiang; Liu, Chenlu; Deng, Shuman; Tang, Meng; Zhou, Chunyu; Huang, Zhiqiang; Yang, Maolin; Zhao, Bin
Abstract: With the increase of the azo pigment wastewater, it is necessary to seek an efficient and sustainable treatment method to address issues of damaging water ecosystems and human health. In this work, organic representing azo dye Acid Orange 7 (AO7), heavy metal representing hexavalent chromium (Cr(VI)), and inorganic representing ammonia nitrogen (NH4 + -N) were selected to roughly simulate the azo pigment wastewater. The simultaneous decontamination of multi-target pollutants by 700 °C pyrolyzed peanut shell biochar (BC) with persulfate (PDS) was evaluated. The results showed that AO7, Cr(VI) and NH4 + -N could finally reach 100%, 85% and 30% removal ratios separately in the BC/PDS/mixed pollutants system under certain basic conditions. Functional groups (hydroxyl groups (C–OH) and carboxylic ester/lactone groups (O–C=O)) were found by XPS as competing sites for adsorption and activation and were gradually consumed as the reaction proceeded. Combining a series of experiments results and EPR analysis, it was found that AO7 removal worked best and it relied on both the radical pathway (including SO4 −, OH, O2 −, but not 1 O2 ) and adsorption. Cr(VI) was mainly adsorbed and reduced by BC surface to form Cr(OH)3 and Cr2 O3, and the remaining part could be reduced by O2 −, followed by OH. NH4 + -N was removed primarily by the radical same as AO7. Meanwhile, the three target pollutants have a co-competitive mechanism. Specifically, they competed for radicals and adsorption sites simultaneously, while the presence of AO7 and NH4 + -N would consume the generated oxidizing radicals and further promote the removal of Cr(VI). The fixed-bed reactor simulated the continuous treatment of wastewater. Various anions (chloride (Cl − ), nitrate (NO3 − ), carbonate (CO3 2− ), and hydrogen phosphate (HPO4 2− )) interfered differently with the pollutant removal. These findings demonstrate a new dimension of BC potential for decontamination of azo pigment wastewater. Graphical abstract: Image 1 Highlights: C–OH and O–C=O on BC were competing sites for pollutants adsorption and PDS activation. Competitive and synergistic mechanism existed among AO7, NH4 + -N and Cr(VI). AO7 and NH4 + -N degradation were both dominated by SO4 . −, OH and O2 − . Cr(VI) decontamination was dominated by adsorption, followed by O2 − . . The fixed-bed reactor and anion interference were explored as supplementary applications.